HUBUNGAN DUKUNGAN DAN POLA KOMUNIKASI KELUARGA DENGAN TINGKAT KECEMASAN PADA PASIEN DENGAN PENYAKIT TIDAK MENULAR - Sonia Danti, (2022)
The increasing prevalence of non-communicable diseases throughout the world causes anxiety for sufferers so that it requires efforts from families to reduce them. This study aims to determine the relationship between support and family communication patterns with anxiety levels in patients with non-communicable diseases at the RS Rumah Sehat Terpadu Dompet Dhuafa Bogor. This research is quantitative with analytical descriptive method and cross sectional approach. The sampling technique used purposive sampling so that the number of samples was 180 people. The results of the analysis using Spearman showed a relationship between support and family communication patterns with anxiety levels in patients with non-communicable diseases with p-value 0.000 and coefficient value -0.452 on family support variable with anxiety level, and coefficient value -0.383 on communication pattern variable with anxiety level. Patients with non-communicable diseases can increase knowledge about the disease they are experiencing, in addition support from family and effective communication are also needed to reduce the level of anxiety felt by these patients.